PEMBERDAYAAN SISWA MALAS, NAKAL, PELAKU DAN KORBAN BULLYING MELALUI PELATIHAN DAN PENDAMPINGAN MENULIS ASYIK REFLEKTIF - Alamsyah, Muh. Nur; Alfiyah, Faridah; Anugerah, Muh. Fahmi; Nabilah, Naimah Zhahratun; Sultan, Sultan (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The partners in this service program are students who have behavioral problems, such as laziness, delinquency, and bullying, which have an impact on their academic performance and social relationships. A total of 37 students exhibited deviant behavior, with 15 students selected for special attention due to the more serious level of the problem. The program aimed to change the students' negative behaviors into more positive ones through cathartic, writing, fun, and reflective approaches. Students are expected to be able to reflect on their actions and increase awareness of the importance of personal responsibility within the school environment. This program is implemented through five stages: preparation, problem handling intervention, writing assistance with the cathartic method of reflective fun writing, preparation of written works in the form of an ISBN book, and a comprehensive evaluation of student development during the program. Training and mentoring were conducted in 15 in-person and online meetings. The program results showed an increase in students' awareness of the impact of their behavior, indicated by significant changes in the aspects of discipline, positive attitudes, and improved reflective writing skills. Students also published inspiring books as a tangible manifestation of empowerment through this program. This program successfully provides an effective solution to address behavioral problems through the cathartic method of reflective fun writing, which not only helps students' behavior change, but also empowers them through written works that benefit themselves and the school environment.